Akuntabilitas Pengelolaan Dana Nagari di Nagari Ulakan Kecamatan Ulakan Tapakis Kabupaten Padang Pariaman - Zhalul, Arief; Malau, Hasbullah (PUBLICNESS: Journal of Public Administration Studies, 2024)
The purpose of this article is to highlight the management of village funds in Nagar Ulakan based on Permendagri No. 113/2014 on village financial management. The research method used in this study is a descriptive qualitative method. The results show that the management of village funds has only reached the planning stage, while the implementation, administration, reporting, and accountability stages have not been in accordance with the provisions. The main obstacles in village financial management are related to human resources and reporting delays. Efforts made to overcome these obstacles include developing a selection system for lower-level officials, as well as improving education and training. Although the principles of village financial management such as transparency, accountability, and participation have been  ecognized, their implementation has not been effective. Accountability is measured as the obligation to report the management of village funds from beginning to end through periodic reporting. Although Nagari Ulakan refers to Permendagri No. 113 of 2014, the implementation of accountability and transparency of village fund management still needs to be improved.